Memory Formation in Isaiah 40-55 : Poetic Reimagination that Accomplishes Comfort - Roberts, Megan C., (Biblical Interpretation Series ;, 2025)
While scholars recognize that comfort and memory are dominant, interconnected themes in Isaiah 40-55, the phenomenon of collective memory itself has not received specific attention to clarify why memory is connected to comfort. Sociological memory studies and trauma theory fill this methodological gap by explaining the nature of memory framework formation within Second Isaiah. Jacob/Israel and Zion, as poetic figures, exemplify the broken memory frameworks of exilic Judeans that do not lead to comfort. This analysis of Isa 40-55, then, reveals Yahweh's poetic process by which he re-forms his people's memory frameworks so that they can receive comfort.